2016
DOI: 10.1007/s11356-016-6653-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static magnetic fields and phloretin on antioxidant defense system of human fibroblasts

Abstract: The available evidence from in vitro and in vivo studies is deemed not sufficient to draw conclusions about the potential health effects of static magnetic field (SMF) exposure. Therefore, the aim of the present study was to determine the influence of static magnetic fields and phloretin on the redox homeostasis of human dermal fibroblasts. Control fibroblasts and fibroblasts treated with phloretin were subjected to the influence of static magnetic fields. Three chambers with static magnetic fields of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…The available evidence from in vitro and in vivo studies is considered inadequate to decide about the potential impact of SMF exposure because contradictory results were reported regarding the effect of SMF on antioxidant enzymes and oxidative stress. Additionally, the mechanism of action which SMFs exert on cells still remains undisclosed [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The available evidence from in vitro and in vivo studies is considered inadequate to decide about the potential impact of SMF exposure because contradictory results were reported regarding the effect of SMF on antioxidant enzymes and oxidative stress. Additionally, the mechanism of action which SMFs exert on cells still remains undisclosed [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, PH has high safety margin with less side effects. Several previous in vitro and in vivo studies showed that PH is not toxic to several non-cancerous cells such as epithelial breast cells MCF10A [18] and normal human dermal fibroblast [19]. It has also been reported that PH scavenges ONOO- and inhibits lipid peroxidation in rat liver microsomes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of the cells was assessed after 24 hr and 48 hr of CGA treatment. Two experiments were performed as was previously reported (Pawłowska‐Góral et al., 2016).…”
Section: Methodsmentioning
confidence: 99%